2000
DOI: 10.1002/1526-968x(200008)27:4<159::aid-gene50>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Role of the zebrafishtrilobite locus in gastrulation movements of convergence and extension

Abstract: Convergence and extension are gastrulation movements that participate in the establishment of the vertebrate body plan. Using new methods for quantifying convergence and extension movements of cell groups, we demonstrate that in wild-type embryos, dorsal convergence of lateral cells is initially slow, but speeds up between the end of the gastrula period and early segmentation. Convergence and extension movements of lateral cells in trilobite mutants are normal during the gastrula period but reduced by early se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 55 publications
11
93
0
Order By: Relevance
“…We previously observed that lateral mesodermal cells (80% epiboly, 8.4 hpf) migrated primarily dorsally, frequently with substantial animal or vegetal bias and showed quite variable net dorsal speed (Jessen et al, 2002). Finally, our previous studies in which lateral mesodermal cells labeled at early gastrulation were visualized at early segmentation stages provided another hint of difference in path orientation along the AnVg axis of the mesoderm (Sepich et al, 2000;Topczewski et al, 2001). The labeled cell group moved toward the dorsal midline, forming a broken line along the animal-vegetal (or anterior-posterior) axis.…”
Section: Movement Behaviors Of Lateral Mesodermal Cells Vary Along Thmentioning
confidence: 78%
See 4 more Smart Citations
“…We previously observed that lateral mesodermal cells (80% epiboly, 8.4 hpf) migrated primarily dorsally, frequently with substantial animal or vegetal bias and showed quite variable net dorsal speed (Jessen et al, 2002). Finally, our previous studies in which lateral mesodermal cells labeled at early gastrulation were visualized at early segmentation stages provided another hint of difference in path orientation along the AnVg axis of the mesoderm (Sepich et al, 2000;Topczewski et al, 2001). The labeled cell group moved toward the dorsal midline, forming a broken line along the animal-vegetal (or anterior-posterior) axis.…”
Section: Movement Behaviors Of Lateral Mesodermal Cells Vary Along Thmentioning
confidence: 78%
“…1AB) showed that between shield stage and 80% epiboly (6.0 -8.4 hpf), labeled lateral cell populations converge slowly, about 15°in 2.5 h, while undergoing moderate extension (Sepich et al, 2000;Myers et al, 2002). In these experiments, one-cell embryos were injected with caged fluorescein dextran.…”
Section: Lateral Mesendodermal Cells Do Not Engage In Convergence At mentioning
confidence: 94%
See 3 more Smart Citations